2015
DOI: 10.1080/09168451.2015.1015952
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrochemical analysis of a hyperthermophilic microbial fuel cell generating electricity at temperatures above 80 °C

Abstract: We examined whether a hyperthermophilic microbial fuel cell (MFC) would be technically feasible. Two-chamber MFC reactors were inoculated with subsurface microorganisms indigenous to formation water from a petroleum reservoir and were started up at operating temperature 80 °C. The MFC generated a maximum current of 1.3 mA 45 h after the inoculation. Performance of the MFC improved with an increase in the operating temperature; the best performance was achieved at 95 °C with the maximum power density of 165 mWm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…Since the MFC configurations, specifically the type of cathode, were different in the reported literature, comparing current densities (normalized with respect to geometric area of the anode) would be more meaningful rather than the usual metric such as power density. The current density of 667 mA m À2 measured in this study using Pf cells was higher than the 450 mA m À2 measured previously (Fu et al, 2015) using a mixed microbial culture from a petroleum reservoir in a similar type of MFC operated at 80 C. The maximum current density reported so far in MFCs operated above 55 C is 1500 mA m À2 using C. nitroreducens (Fu et al, 2013), where several cycles of medium were fed and the developed biofilm were found to generate a stable current for a time scale of more than 400 h. However, in our case, the experiments were conducted mainly as a batch study for a proof of concept to show the interaction of Pf with MFC electrode to generate electricity and no actual electrochemical or engineering efforts with respect to the MFC design/configuration or process optimizations have been made to maximize the current density of the system. Furthermore, in addition to the experiments reported here, future studies on exoelectrogenicity of hyperthermophiles such as Pf will help identify the possible electron acceptors that they can utilize.…”
Section: Extracellular Electron Transport Pathways Of P Furiosuscontrasting
confidence: 75%
See 1 more Smart Citation
“…Since the MFC configurations, specifically the type of cathode, were different in the reported literature, comparing current densities (normalized with respect to geometric area of the anode) would be more meaningful rather than the usual metric such as power density. The current density of 667 mA m À2 measured in this study using Pf cells was higher than the 450 mA m À2 measured previously (Fu et al, 2015) using a mixed microbial culture from a petroleum reservoir in a similar type of MFC operated at 80 C. The maximum current density reported so far in MFCs operated above 55 C is 1500 mA m À2 using C. nitroreducens (Fu et al, 2013), where several cycles of medium were fed and the developed biofilm were found to generate a stable current for a time scale of more than 400 h. However, in our case, the experiments were conducted mainly as a batch study for a proof of concept to show the interaction of Pf with MFC electrode to generate electricity and no actual electrochemical or engineering efforts with respect to the MFC design/configuration or process optimizations have been made to maximize the current density of the system. Furthermore, in addition to the experiments reported here, future studies on exoelectrogenicity of hyperthermophiles such as Pf will help identify the possible electron acceptors that they can utilize.…”
Section: Extracellular Electron Transport Pathways Of P Furiosuscontrasting
confidence: 75%
“…strain JR (Wrighton et al, 2008), Thermincola ferriacetica (Marshall and May, 2009), and Calditerrivibrio nitroreducens (Fu et al, 2013) were shown to generate electricity in MFCs that are operated at a temperature greater than 50 C. Operating an MFC at an elevated temperature has many advantages over ambient temperature systems, such as higher reaction rates (both chemical and electrochemical), minimal risk of contamination from ubiquitous mesophilic microorganisms and ease of maintenance of reducing anaerobic conditions due to lower solubility of oxygen at higher temperatures (Ieropoulos et al, 2005;Mathis et al, 2008;Wrighton et al, 2008). Recently, a mixed microbial culture obtained from the sub-surface of a petroleum reservoir was used as a biocatalyst to examine electricity generation in a MFC that was operated at temperatures above 80 C (Fu et al, 2015). In addition, a MFC was installed at a hydrothermal vent field and continually operated for 6 months (Girguis and Holden, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that SILMs seem to be advantageous in special bioelectrochemical applications, such as hyper-thermophilic MFCs (>80 • C) [40]. In these systems, extreme thermophilic bacteria serves as biocatalysts; however, common proton exchange membranes (PEM), such as Nafion, fail to stay hydrated for proper functioning.…”
Section: Research Progress With Supported Ionic Liquid Membranes For mentioning
confidence: 99%
“…These exoelectrogenic microorganisms are capable of extracellular electron transfer to a solid electrode, which are used in Microbial Electrochemical Technologies (METs) such as Microbial Fuel Cells (MFC) and microbial electrolysis cells (MEC) (Doyle and Marsili, 2015). In the past years, exoelectrogenic activity has been reported in almost 100 microbial species which are mostly affiliated with the bacterial phylum Proteobacteria (Koch and Harnisch, 2016 (Fu et al 2015) and at 80 °C from Red Sea brine pools (Shehab et al 2017) on the anode of MFC systems.…”
Section: Introductionmentioning
confidence: 99%
“…sources(Alain et al 2010). A close related species, Thermodesulfobacterium commune has already been identified in EAB on electrode of a MFC(Fu et al 2015) …”
mentioning
confidence: 97%